The impact of technical change in agriculture on human fertility: district-level evidence from India - Vosti, Stephen A.; Witcover, Julie; Lipton, Michael (International Food Policy Research Institute, 1994)
Green Revolution technologies were developed and promoted to boost food supplies and foster development, both of which were expected to create breathing space for achieving demographic transitions in developing countries through lowered human fertility. Little comprehensive research, however, has been done on the effects of those technologies themselves on human fertility -- leaving unanswered the question of whether particular types of agricultural technologies were actually increasing, or decreasing, this demographic "breathing space." This paper uses District-level data from rural India on agricultural change (from 1961 to 1981) and changes in human fertility (from 1971 to 1981) to assess the impact of the former on the latter, with particular emphasis on high yielding (HYV) Green Revolution technologies. Modifying a conceptual framework derived from theory on the determinants of fertility, and estimating a reduced form model that explicitly accounts for endogeneity of real wage growth, we find that, while socio-cultural and demographic factors were the strongest determinants of fertility change: a) Green Revolution and related technologies did have an impact on fertility change; b) that the magnitude and direction of this impact was technology specific; and c) that the impact was only partially due to the effect of the new technologies on changes in real wage growth.